Functional Microorganisms Drive the Formation of Black-Odorous Waters - Yuchen Wu; Wenjing Wang; Xiaozhu Liu; Yanqing Sheng (Microorganisms, 2024)
Black-odorous waters are water bodies that are noticeably abnormal in color or emit unpleasant odors. River water pollution and ecological degradation have gradually emerged with urbanization and rapid economic development, and BOW has become frequent. The black-odorous evolution of urban water bodies is a serious environmental problem in many areas, posing a serious threat to both human health and the ecological environment. Functional microorganisms are closely related to the formation of black-odorous phenomena in water bodies, but the understanding of the mechanisms by which functional microorganisms influence the formation of BOW is very limited. In this study, water samples from the Guangdang River in Yantai, Shandong Province, China, were collected as the bacterial solution in the study, and how environmental factors and functional microorganisms affect the formation of black smelly water was investigated by artificially simulating black smelly water. The results indicated that different environmental factors have different effects on the formation of BOW. Anaerobic conditions accelerated the formation of BOW, and species diversity and species abundance were lowest under this condition. Hydraulic disturbance and nitrate effectively mitigated the BOW phenomenon, in which species diversity and species abundance were higher; controlling either of these variables was effective in mitigating the BOW phenomenon. Desulfobacterota played a key role in the formation of BOW, and reducing the proportion of Desulfobacterota in the microbial community could effectively improve the water quality. Possible directions of electron transfer in the process were hypothesized. This study contributes to identifying the biological driving factors for black-odorous evolution, presents insight for preventing BOW formation, and provides a scientific basis for subsequent BOW management.